Qatar and UAE in Peacemaking and Peacebuilding - Freer, Courtney (My University, 2022)
This paper seeks to highlight ways in which Qatari and Emirati peacemaking/ peacebuilding engagement is qualitatively different from other states’ or international organisations’ efforts in this sphere. The main questions explored were how Qatar and Emirati approaches to peacemaking/peacebuilding are unique, whether or to what extent their engagement has been useful to the resolution of conflicts, and how the FCDO can leverage these states’ interest in this sphere. This research uncovered five main characteristics of peacemaking/ peacebuilding done by these small but wealthy states. First, small states, unlike regional or global superpowers, tend to have fewer direct links to the conflicts themselves, and so they can be selective about cases in which they become involved. Second, the fact that both states benefit from immense hydrocarbon wealth undoubtedly aids their ambitious goals abroad. Third, efforts at peacekeeping in the states analysed here tend to be guided by a desire to distinguish themselves abroad, something of statebuilding through foreign policy. Fourth, the trend towards the involvement of Qatar and the UAE in regional peacemaking/peacebuilding, as well as potential build-up of military capacity, is likely to accelerate, given perceptions of UK and US withdrawal from the region. Fifth, a lack of institutional depth in these small states means that policies are at times abandoned quickly and without explanation and that personal ties are of critical importance.
Keywords: Global Transitions; Peace Processes; Qatar; UAE